Minding the Gap: eBook package purchasing. Issue 4 (5th October 2015) - Kerby, Erin E.; Trei, Kelli
Abstract : Purpose: – This study aims to highlight practical considerations to be made when choosing an eBook package for an institution. Many academic libraries purchase eBooks bundled in packages, either as a time- or cost-saving measure or to build a new subject collection. Design/methodology/approach: – The authors searched the Web sites of six major publishers for information on eBook packages, including subject coverage, digital rights management restrictions and usage allowances. The analysis also includes a potential overlap between related subject collections and the ability to purchase titles individually. Findings: – Usage allowances, digital rights management restrictions and purchasing options vary considerably from publisher to publisher. There was title overlap between related subject packages found in some publishers. In response to user preferences and needs, many publishers are loosening restrictions on their eBook content, which make purchasing packages a more attractive option for libraries. Originality/value: – The landscape of eBook publishing is rapidly changing, which can complicate purchasing decisions. The detailed comparison provided by this study can be used to assist collections developers in making purchasing decisions best suited to their library and avoiding pitfalls such as duplicate purchases.